Case of Millennial Generation: The Influence of Customer Satisfaction, Service Quality, and Price on Transjakarta Customer Loyalty in North Bekasi City - Agus Dharmanto; Muhammad Richo Rianto; M Fadhli Nursal (East Asian Journal of Multidisciplinary Research, 2022)
This study is to measure the effect of customer satisfaction, service quality, and price on the loyalty of millennial generation trans Jakarta users in the city of North Bekasi. This study uses quantitative research methods where the millennial generation of trans-Jakarta users in the city of North Bekasi are the objects. This study uses a non-probability sampling technique and uses a sample of 100 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 4.0. The results of this study indicate that customer satisfaction has an effect on customer loyalty of millennial generation trans Jakarta users in North Bekasi city, while service quality and price have no effect on customer loyalty of millennial generation trans Jakarta users in northern Bekasi city. This study has limited research objectives that are only carried out on millennial generation trans Jakarta users in North Bekasi. This is used as a suggestion for future researchers. The novelty in this study combines the variables of customer satisfaction, service quality, and price on the loyalty of millennial generation trans Jakarta users in the city of North Bekasi.